High frequency of cholecystitis in dogs with gallbladder mucocoele in Hong Kong. (September 2022) - Hill, F.I.; Speelman, J.P.; Hui, K.K.L.; Nekouei, O.; Beczkowski, P.; Barrs, V.R.
Abstract: The aims of this retrospective study were to characterise the epidemiological, clinical, histopathological, and microbiological findings as well as surgical outcomes in dogs admitted to a specialist veterinary hospital in Hong Kong for surgical management of gallbladder mucocoele (GBM). Inclusion criteria were cases with histopathological diagnosis of GBM and accompanying abdominal imaging, serum biochemistry, bile culture, and liver biopsy histology results. Fifty-six cases met the inclusion criteria. The median age at diagnosis was 12 years (range, 5–16 years). Miniature or toy pure-breed dogs were most commonly affected, including Poodles, Pomeranians, Schnauzers, Bichon frises and Chihuahuas. However, no breed was over-represented compared with their expected proportions among annual hospital admissions. Histological evidence of cholecystitis was present in 84% of cases, including acute cholecystitis in 18%, chronic cholecystitis in 37.5%, acute on chronic cholecystitis in 28% and acute with necrosis in 6%. The most common liver lesions were cholestasis in 64%, along with portal fibrosis in 55%, oedema in 50% and bile duct hyperplasia in 50%. Bile culture was positive in 29.6% of cases. Escherichia coli and Enterobacter species were most commonly isolated. Stentrophomonas maltophili was cultured from one case. Of the 16 cases where bacteria were isolated from bile culture, 94% had evidence of chronic cholecystitis and 81% had evidence of cholangiohepatitis. Fifty dogs (89.3%) survived to discharge including 5/5 dogs with ruptured gallbladders. Of 34 dogs with follow-up data, 21/34 (61.8%) were still alive 12 months later. Gallbladder mucocoeles were frequently associated with both acute and chronic inflammation. High survival rates to discharge were achieved. Highlights: This canine population had no breed predisposition for gallbladder mucocoele. Cholecystitis was a common comorbidity (84%) in dogs with gallbladder mucocoele. Positive bacterial culture of bile occurred in 29.6% of dogs with mucocoeles. High survival rates to discharge were achieved (89%) following cholecystectomy.